2021
DOI: 10.3390/molecules26071919
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Zinc Oxide Nanoparticles from Acacia nilotica (L.) Extract to Overcome Carbapenem-Resistant Klebsiella Pneumoniae

Abstract: Recently, concerns have been raised globally about antimicrobial resistance, the prevalence of which has increased significantly. Carbapenem-resistant Klebsiella pneumoniae (KPC) is considered one of the most common resistant bacteria, which has spread to ICUs in Saudi Arabia. This study was established to investigate the antibacterial activity of biosynthesized zinc oxide nanoparticles (ZnO-NPs) against KPC in vitro and in vivo. In this study, we used the aqueous extract of Acacia nilotica (L.) fruits to medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
6
15
2
Order By: Relevance
“…The two types of zinc Nano solutions, where the concentrations of commercial and synthetic zinc nanoparticles, which are 2.5, 5, 10, 20 mg/ml, gave inhibition rates of 10, 13, 15, 17 mm, respectively for the solution of biosynthetic zinc particles, while the commercial zinc particles solution gave the rates of retarding diameters are 0, 12, 12, 13 mm, respectively, it was observed that the highest inhibitory activity of the biosynthetic zinc nanoparticles solution was at a concentration of 20 mg/ml with an average inhibition diameter of 17 mm, while the lowest inhibitory activity was at a concentration of 2.5 mg/ml with an average inhibition diameter of 10 mm towards the above bacteria, while the commercial zinc nanoparticles solution gave the highest inhibitory activity was at a concentration of 20 mg/ml with an average inhibition diameter of 13 mm, and the lowest inhibitory activity was at a concentration of 5 mg/ml with an average inhibition diameter of 12 mm. The result we obtained is in agreement with the findings of Rasha et al (2021), where zinc nanoparticles biosynthesized by acacia plant extract showed an inhibitory effect on K. pneumoniae bacteria. It also agrees with the findings of Farzana and Iqra, (2017) who observed the zinc nanoparticle solution has inhibitory activity against K. pneumonia.…”
Section: Transmission Electron Microscope For Zinc Nanoparticles (Tem)supporting
confidence: 92%
“…The two types of zinc Nano solutions, where the concentrations of commercial and synthetic zinc nanoparticles, which are 2.5, 5, 10, 20 mg/ml, gave inhibition rates of 10, 13, 15, 17 mm, respectively for the solution of biosynthetic zinc particles, while the commercial zinc particles solution gave the rates of retarding diameters are 0, 12, 12, 13 mm, respectively, it was observed that the highest inhibitory activity of the biosynthetic zinc nanoparticles solution was at a concentration of 20 mg/ml with an average inhibition diameter of 17 mm, while the lowest inhibitory activity was at a concentration of 2.5 mg/ml with an average inhibition diameter of 10 mm towards the above bacteria, while the commercial zinc nanoparticles solution gave the highest inhibitory activity was at a concentration of 20 mg/ml with an average inhibition diameter of 13 mm, and the lowest inhibitory activity was at a concentration of 5 mg/ml with an average inhibition diameter of 12 mm. The result we obtained is in agreement with the findings of Rasha et al (2021), where zinc nanoparticles biosynthesized by acacia plant extract showed an inhibitory effect on K. pneumoniae bacteria. It also agrees with the findings of Farzana and Iqra, (2017) who observed the zinc nanoparticle solution has inhibitory activity against K. pneumonia.…”
Section: Transmission Electron Microscope For Zinc Nanoparticles (Tem)supporting
confidence: 92%
“…This could be because Gram-positive bacteria have thicker, more solid multiple layers of peptidoglycan in their cell walls, which inhibits nanoparticles from penetrating [47]. In recent studies, ZnO NPs produced from Butea monsoperma, Acacia nilotica (L.), and Plectranthus amboinicus leaf extracts demonstrated high antibacterial activity against Pseudomonas aeruginosa, Klebsiella Pneumoniae, and Staphylococcus aureus [48][49][50], suggesting that traditional medicinal extract-mediated ZnO NP synthesis could be extremely beneficial for the medical industries.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…Additionally, the Vyazovkin free kinetics model (2) [42] was used to determine the activation energy (E a ) of the degradation process. For this purpose, the TG measurements were repeated in the same conditions but with different heating rates (5,15,20…”
Section: Characterization Of Zno Particlesmentioning
confidence: 99%
“…The extracts are used as either stabilizing or reducing agents. Some of the methods involve using the leaves of plants such as jackfruit (Artocarpus heterophyllus) [2] or Carissa carandas [3], flowers like Anchusa italica [4], the fruits of plants, including Acacia nilotica [5], the peels of the fruits (e.g., a banana (Musa paradisiaca) peel [6]), or the root of the plant like Berberis vulgaris [7].…”
Section: Introductionmentioning
confidence: 99%